FINANCIAL DISTRESS ANALYSIS AND COMPARISON OF ALTMAN Z-SCORE, SPRINGATE, AND GROVER MODELS AT PT SRITEX FOR THE PERIOD 2019-2023 - Anisah, Dede Ayu; Delilah, Laura Natasha; Maiyaliza, Maiyaliza (Journal of Management Small and Medium Enterprises (SMEs), 2025)
This study looks at how well of the Grover models, Springate, and Altman Z-Score in forecasting financial distress at PT Sritex and how useful they are in the Indonesian textile industry. The approach that was taken was descriptive quantitative, and it made employment of supplementary data from the IDX website from the perspective of financial accounts for the years 2019–2023. The Altman Z-Score model's 0% accuracy indicates its inefficiency, in contrast, the Springate and Grover models both have an accuracy of forty percent. Despite the fact that the most recent two models provide a more realistic representation of the company's current financial status, the prediction error rate is still substantial (type error 60%). This shows that the Altman Z-Score is less reliable, while Springate and Grover are more accurate, although still limited. Therefore, it is not recommended to rely on only one model in assessing a company's financial risk. This research also opens up opportunities for further studies with a wider range of industries to obtain more comprehensive and accurate results. Keywords: Financial distress, Grover, Springate, Altman Z-Score